Analisis Kapasitas Seismik Gedung Eksisting Beton Bertulang Dengan Dinding Bata - Lestari, Dinda; Maidawati, Maidawati; Ridwan, Muhammad (Universitas Andalas, 2024)
West Sumatra is one of the provinces in Indonesia with an area that is very prone to earthquakes that can cause damage and even collapse reinforced concrete buildings. Therefore, an evaluation of the seismic capacity of buildings in West Sumatra was conducted. The purpose of this study was to evaluate the seismic capacity of the FMIPA Lecture Building, Padang State University by taking into account the influence of brick walls. The evaluation was guided by the Japanese standard, Standard for Seismic Evaluation of Existing Reinforced Concrete Building, 2001, using the level two method. The evaluation was carried out only on the first floor where the greatest shear force occurs in the building structure with calculations in two directions, namely the East and North directions. The seismic capacity is expressed by the basic seismic index value of the building, E0 which is obtained from the relationship between lateral strength and structural ductility. As a result, the basic seismic index value for the North direction is 0.48 with a lateral strength index of 0.49 and a ductility index of 1.0. In the East direction the basic seismic index value is 0.38 with a lateral strength index of 0.41 and a ductility index of 0.92. So the FMIPA Lecture Building, Padang State University has sufficient seismic capacity to withstand an earthquake.